ANALISIS PENGARUH PENDAPATAN ASLI DAERAH, DANA BAGI HASIL DAN JUMLAH PENDUDUK TERHADAP ANGGARAN BELANJA MODAL KABUPATEN/KOTA DI PROVINSI RIAU - Nihayatul Fitriana; Sudarti Sudarti (Jurnal Ilmu Ekonomi JIE, 2018)
The purpose of this research is to know the effect of Local Revenue, Profit Sharing Fund and Population to the allocation of Capital Expenditure of regency / city in Riau Province in 2012-2016. The population used in this study is all districts / cities in Riau Province, amounting to 10 districts and 2 cities, with data sources from BPS. This test uses multiple linear regression analysis techniques with the help of Eviews application. The result with multiple linear regression research shows that the local revenue, profit sharing and population influence on the allocation of capital expenditure with R-Square of 0.87 or 87% that the variables in the research model can predict the allocation of capital expenditure while 13% by other variables outside the research model.Keywords : Local Revenue, Revenue Sharing Fund, total population, Capital Expenditure.